Pearl Millet: Potential Alternative for Grain and Forage for Livestock in Semi-arid Regions of Mexico - Maiti, Ratikanta; Rodríguez, Humberto González (International Journal of Bio-resource and Stress Management, 2010)
Researches undertaken on the introduction and evaluation of some tropical pear millet germplasms (91) and cultivars (15) revealed that tropical pearl millet could be a potential crop for production of fodder and grains for livestock/poultry in semi-arid north-east of Mexico. Crops were well adapted in semi-arid regions of north-east Mexico, and gave high yield of fodder and grain with good nutritional values.